The use of infrared thermography to detect the skin temperature response to physical activity. (October 2015) - Tanda, G
Abstract: Physical activity has a noticeable effect on skin blood flow and temperature. The thermal regulatory and hemodynamic processes during physical activity are controlled by two conflicting mechanisms: the skin vasoconstriction induced by the blood flow demand to active muscles and the skin vasodilation required by thermoregulation to increase warm blood flow and heat conduction to the skin. The time-evolution of skin temperature during exercise can give useful information about the adaptation of the subject as a function of specific type, intensity and duration of exercise. In this paper, infrared thermography is used to investigate the thermal response of skin temperature during running exercise on treadmill for a group of seven healthy and trained runners. Two different treadmill exercises are considered: a graded load exercise and a constant load exercise; for both exercises the duration was 30 minutes. Within the limits due to the relatively small size of the sample group, results typically indicate a fall in skin temperature during the initial stage of running exercise. As the exercise progresses, the dynamics of the skin temperature response depends on the type of exercise (graded versus constant load) and probably on the level of training of the subject.